Measuring Organizational Legitimacy in Social Media: Assessing Citizens’ Judgments With Sentiment Analysis - Etter, Michael; Colleoni, Elanor; Illia, Laura; Meggiorin, Katia; D’Eugenio, Antonio (SAGE Publications Ltd, 2018)
Conventional quantitative methods for the measurement of organizational legitimacy consider mainly three sources that make judgments about organizations visible: news media,accreditation bodies,and surveys. Over the last decade,however,social media have enabled ordinary citizens to bypass the gatekeeping function of these institutional evaluators and autonomously make individual judgments public. This inclusion of voices beyond functional and formally organized stakeholder groups potentially pluralizes the ongoing discussions about organizations. The individual judgments in blogs,tweets,and Facebook posts give indication about the broader fit between an organization’s perceived behavior and heterogeneous social norms and therefore constitute an indicator of organizational legitimacy that can be accessed and measured. We propose the use of social media data and sentiment analysis to study the affect-based responses to organizational actions by citizens. We critically discuss and compare the method with existing quantitative methods for legitimacy measurement and apply them to a recent case in the banking industry. We discuss the value of the method for studying the process of legitimacy construction as the expression and negotiation of normative judgments about organizations by various evaluators. © 2017,© The Author(s) 2017.
Keywords: 63 Sociología; ODS 9 - Industria, innovación e infraestructura